CLINICAL LABORATORIES IN THE ERA OF THE COVID-19 PANDEMIC: AN ANALYSIS OF EXPERIENCES IN SERBIA: Clinial labortories and COVID-19 - Stanković, Sanja; Asanin, Milika (Srpski medicinski časopis Lekarske komore, 2021)
The COVID-19 pandemic represents one of the most serious public health threats that our world has faced in recent history. In the global fight against these pandemics, clinical laboratories play a significant role. This paper is based on the experiences of the Center for Medical Biochemistry of the University Clinical Centre of Serbia. Using a mixed method, the study shed light on the many challenges the Centre faced during the pandemic, it outlines the implementation of change and makes recommendations for functioning during COVID-19 pandemic and in the post-COVID era.